SUBJECTIVE WELL-BEING PADA LANSIA - Asniti Karni (Institut Agama Islam Negeri Bengkulu, 2018)
Subjective well-being for the elderly is a very urgent matter because with the elderly having a higher assessment of happiness and life satisfaction, the brand tends to act happier and more satisfied. Subjective well-being is a person's perception of his life experience, which consists of cognitive evaluation and affection towards life and presenting in psychological well-being. According to the author, Subjective Well-Being is a form of gratitude in the process of self-evaluation of happiness and life satisfaction that is felt so that the individual himself feels comfort and balance which makes him a complete human being. The support from surrounding people becomes a benchmark and the support of these individuals can enjoy what they really have. Eldery People have good subjective well-being, if their needs are met, have self-esteem, optimism, an acceptable sense of control, openness, positive relationships with others, and an understanding of the meaning and purpose of life. A pleasant feeling is more than a sad feeling. When the elderly feel homesick, they are able to control feelings of sadness by remembering God. Elderly people are said to have high subjective well-being if they experience life satisfaction, often feel joy and rarely feel unpleasant emotions such as sadness or anger. Conversely, individuals are said to have low subjective well-being if they are not satisfied with their lives, experience a little excitement and affection, and more often feel negative emotions.